Algorithm analysis development of handwriting - Зарубенко, Олексій Олексійович (Technology audit and production reserves, 2014)
Two algorithms that allow to recognize handwriting are shown in the article. These approaches are considered the most relevant off-line recognition, which is based on the handwriting recognition from scan image of profiles, agreements, statements and other documents. Development is done to promote recognition not only in document flow, but also in the field of artificial intelligence that surrounds subsequently able to analyze a human-written text. It was found that both the description algorithm can give us positive feedback for recognition. With the result of more than 90 % of the work on pattern recognition, at least one of the approaches will be fully achieved its investigation aim and will only improve the knowledge base, which is then able to provide for artificial intelligence an opportunity to learn through books and letters improving the percentage of recognition.